Vita brevis : la carta de Floria Emilia a Aurelio Agustín - Gaarder, Jostein, 1952-; Baggethun, Kirsti; Lorenzo, Asunción; Gaarder, Jostein, 1952- (Madrid : Ediciones Siruela, 2011)
A fictional letter to St. Augustine from his mistress, whom he repudiated in favor of celibacy. Prompted by her reading of his Confessions, the letter mixes nostalgic erotica with feminist criticism of the Church's position on women and love. The couple lived together for 10 years and had a son.
Online resource; title from ePub title page (Digitalia, viewed March 25, 2016)
Keywords: Augustine, -- Saint, Bishop of Hippo -- Fiction; Electronic books